2015
DOI: 10.17645/pag.v3i4.315
|View full text |Cite
|
Sign up to set email alerts
|

Is a European Practice of Mass Atrocity Prevention Emerging? The European Union, Responsibility to Protect and the 2011 Libya Crisis

Abstract: Observers have classified the European Union (EU) as reluctant in its implementation of the "Responsibility to Protect" (R2P) (Task Force on the EU Prevention of Mass Atrocities, 2013). This contribution revisits that argument by employing a more nuanced interpretation of norm implementation than the binary conceptualisation typically applied. By appraising EU reactions to the 2011 Libyan crisis, we investigate whether a "European practice of mass atrocity prevention" is emerging and if so how this relates-or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…29 Put in constructivist terms, the EU has accepted but not yet internalized RtoP as an emerging norm. 30 Scholars have offered many reasons for this apparent failure-from a lack of coordination, clear strategy, and political will to commit the necessary means for protecting people outside its borders, 31 to a disagreement between the strategic cultures of influential member states. 32 It is not my concern to explain the EU's ambivalence with respect to RtoP.…”
Section: Parallel Protection: Eu Rtop and The Statementioning
confidence: 99%
“…29 Put in constructivist terms, the EU has accepted but not yet internalized RtoP as an emerging norm. 30 Scholars have offered many reasons for this apparent failure-from a lack of coordination, clear strategy, and political will to commit the necessary means for protecting people outside its borders, 31 to a disagreement between the strategic cultures of influential member states. 32 It is not my concern to explain the EU's ambivalence with respect to RtoP.…”
Section: Parallel Protection: Eu Rtop and The Statementioning
confidence: 99%
“…Recent scholarship has demonstrated that regional normative operationalization of RtoP is following a process of "norm localization" where RtoP is becoming regionalized, adopting localized adaptations through its operationalization in specific contexts (De Franco & Peen Rodt, 2015;Dembinski & Schott, 2014;Seaman, 2015). As De Franco and Peen Rodt (2015) argue, the institutional implementation that occurs once an organization has formally accepted a norm "can become a field of contestation and explain why norms are sometimes understood differently across or indeed within international organizations" (p. 46). The process of developing formal policy and legal mechanisms, or "implementing" the norm, creates standards of behavior that facilitate assessments of compliance (see Betts & Orchard, 2014;De Franco & Peen Rodt, 2015).…”
Section: Normative Institutionalization To Operational Implementationmentioning
confidence: 99%
“…As De Franco and Peen Rodt (2015) argue, the institutional implementation that occurs once an organization has formally accepted a norm "can become a field of contestation and explain why norms are sometimes understood differently across or indeed within international organizations" (p. 46). The process of developing formal policy and legal mechanisms, or "implementing" the norm, creates standards of behavior that facilitate assessments of compliance (see Betts & Orchard, 2014;De Franco & Peen Rodt, 2015). Moving beyond tracing the political discourse or policy development of RtoP, recent scholarship has attempted to begin addressing its "operational implementation" or reactive practices defined by De Franco and Peen Rodt as "the norm's mainstreaming into existing policies and resource allocation" (2015, p. 46).…”
Section: Normative Institutionalization To Operational Implementationmentioning
confidence: 99%
See 2 more Smart Citations